Citrus Acreage Attrition by County in Florida - Singerman, Ariel (EDIS, 2023)
Citrus greening (HLB) has significantly impacted the Florida citrus industry since it was first detected in 2005. The disease has caused both tree health and yield to decrease significantly over time. In 2022/23, due to the combined impact of the disease and hurricane Ian as well as a freeze in December 2022, the statewide average yield for both Valencia and Non-Valencia oranges is estimated to be approximately 50 boxes per acre, down from 389 and 473 boxes per acre, respectively, since the HLB outbreak. Such figures represent an 87% and 89% decrease for Valencia and Non-Valencia oranges, respectively. For grapefruit, the decline has also been very significant. Such a shocking decrease in yield has occurred despite growers’ multiple efforts to adopt practices in an attempt to deal with the disease —which has caused the cost of production to increase significantly, particularly on a per box basis As a consequence, growers have (on average) been facing losses for a number of seasons, forcing many to exit the industry. Thus, the entire Florida citrus industry has been downsizing. One of the consequences of the industry downsize is the attrition of citrus acreage statewide, which is the focus of the analysis in this article and can be of interest to industry stakeholders and policymakers.